What Role do Preferential Trading Arrangements Play in Cross-Border Worker Mobility? Some Asian Evidence - Gounder, Aruna; Falvey, Rod; Rajaguru, Gulasekaran (Journal of international migration and integration, 2025)
United Nations Economic & Social Commission for Asia Pacific data on bilateral worker flows from ten Asian origin countries is used to estimate a temporary-worker migration equation and test whether a preferential trading arrangement (PTA) between the origin and host country influences the size of that migration flow. We find, first, that worker migrants respond as do other migrants except where countries share a common border; second, that PTAs can have a significant positive effect on worker migration, but only if they include service trade and visa provisions beyond the minimum required of World Trade Organization members; and, third, that while a bilateral labor agreement (BLA) and additional provisions in a PTA are not substitutes, country-pairs are found to prefer the BLA option if they share a common border, but the extended PTA option if they are linguistically and culturally distant. We also find that the negative result commonly found relating geographic distance to PTA formation is reversed when other ‘distance-related’ attributes (linguistic, religious and cultural) are included; that conclusions based on aggregated data may be misleading when applied to sub-samples; and that treating a regional agreement as if it were simply a collection of unrelated bilateral agreements risks overlooking potentially important policy constraints.